2018
DOI: 10.1016/j.applanim.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experience of ramps at rear on the subsequent ability of layer pullets to negotiate a ramp transition

Abstract: In commercial situations, laying hens must negotiate levels to reach resources such as food, water and litter. Providing ramps in aviary systems reduces collisions and resultant keel bone fractures in adults. We investigated whether providing ramps during rear improved the ability of birds to transition between levels. Chicks were reared commercially in two flocks both of which provided access to raised structures from three weeks of age. One flock had no ramps, but the other flock was provided with additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 22 publications
6
18
0
Order By: Relevance
“…The results from this study show that providing ramps during rear in a commercial facility enables chicks to access elevated structures during their first week of life, confirming previous experimental results 14 . Chicks had a preference to use the ramps to access elevated structures and this was observable throughout the rearing period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results from this study show that providing ramps during rear in a commercial facility enables chicks to access elevated structures during their first week of life, confirming previous experimental results 14 . Chicks had a preference to use the ramps to access elevated structures and this was observable throughout the rearing period.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed more low perch jumps up the structures and more jumps down from the low-level perches and slats in the control groups. Behaviours indicating hesitancy have been identified and used in both commercial and experimental studies to look at ramp transitions 11 , 14 , 15 . In this study, the difference in hesitancy like behaviours between the rearing groups suggests that providing access ramps improves the confidence to transition up and down structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, we (Norman et al, 2018) and others (Gunnarsson et al, 2000) have found that early experience of structures such as ramps improves the use of the structures compared to birds that have had no experience, illustrating the importance of early life experiences. However, in these previous studies chicks were reared for a longer time (up to 8 weeks or more) under different rearing conditions.…”
Section: Resultssupporting
confidence: 49%
“…Facilitated access (using ramps or staged perches) may be even more beneficial. Our own work has shown that access to ramps during the rearing period improved ramp transitions in older pullets, shown by reduced hesitancy behaviour and shorter transitioning latencies (Norman et al, 2018). A preference for grid ramps over ladder ramps was found suggesting the type of ramp should also be considered (Pettersson et al, 2017).…”
Section: Introductionmentioning
confidence: 91%